1999
DOI: 10.1016/s1369-5274(99)00033-8
|View full text |Cite
|
Sign up to set email alerts
|

Swarming motility

Abstract: Swarming involves differentiation of vegetative cells into hyperflagellated swarm cells that undergo rapid and coordinated population migration across solid surfaces. Cell density, surface contact, and physiological signals all provide critical stimuli, and close cell alignment and the production of secreted migration factors facilitate mass translocation. Flagella biogenesis is central to swarming, and the flhDC flagellar master operon is the focal point of a regulatory network governing differentiation and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
304
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(312 citation statements)
references
References 57 publications
3
304
0
5
Order By: Relevance
“…subtilis swarmers move over swarm plates in a thin fluid film, and show coordinated movement of swirling and streaming packs Swarmers in P. mirabilis are long filamentous cells and are abundantly flagellated (Fraser & Hughes, 1999), while their equivalents in E. coli and Salmonella (McCarter, 2010) are much less elongated, with only a moderate increase in flagella. Similarly, for B. subtilis on LB plates, cells at the swarm front are not filamentous (Kearns & Losick, 2003;Julkowska et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…subtilis swarmers move over swarm plates in a thin fluid film, and show coordinated movement of swirling and streaming packs Swarmers in P. mirabilis are long filamentous cells and are abundantly flagellated (Fraser & Hughes, 1999), while their equivalents in E. coli and Salmonella (McCarter, 2010) are much less elongated, with only a moderate increase in flagella. Similarly, for B. subtilis on LB plates, cells at the swarm front are not filamentous (Kearns & Losick, 2003;Julkowska et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Such a mode of motility allows bacteria to escape local stresses, translocate to a better nutritional environment and efficiently invade host tissue (Fraser and Hughes, 1999;Rashid and Kornberg, 2000;Harshey, 2003). However, despite the benefits, for many bacterial species the ability to migrate on solid surfaces does not exist or is dependent on high surface wetness and thus, restricted to specific environmental conditions (Wang et al, 2005;Kearns, 2010).…”
mentioning
confidence: 99%
“…This process and other forms of surface motility (reviewed in ref. 9) are found in many bacterial genera (11)(12)(13)(14)(15). Swarmer cells are often hyperflagellated, elongated, and multinucleated.…”
mentioning
confidence: 99%
“…It has been suggested that glycolipid and͞or lipopeptide biosurfactants thereby produced function as wetting agents (16). The migration front is preceded by a visible layer of slime-like extracellular material as observed, for example, for Burkholderia cepacia (12,17). Within the matrix of extracellular polymeric material, the population densities are obviously extremely high (17).…”
mentioning
confidence: 99%